(untitled) (CIPEEX, 2022)
CURRENTLY, LARGE AMOUNTS OF POTHOLES ARE FOUND ON THE STREETS THAT COULD BE FIXED BUT END UP BEING IGNORED, GENERATING SOME ACCIDENTS THAT COULD BE AVOIDED WITH A WELL-ASPHALTED ROAD, NOT ONLY THAT, BUT WE ALSO KNOW HOW ANNOYING IS TO FACE SIGNIFICANT TRAFFIC, WHEN YOU ARE GOING TO WORK FOR EXAMPLE. THEREFORE, THE NAVIGATION APP INITIATIVE IS TO USE THE MOST ADVANCED SOFTWARE ENGINEERING TECHNOLOGIES TO REDUCE THE NUMBER OF POTHOLES ON ROADS AND SHORTEN THE TRAVEL TIME FROM ONE DESTINATION TO ANOTHER. SUCH METHODS WERE BASED ON THE BEST METHODOLOGIES APPLIED WITHIN SOFTWARE ENGINEERING, SUCH AS BPMN, DESIGN THINKING, AND SCRUM, FOR EXAMPLE. THE PURPOSE OF THIS SOFTWARE IS TO PROVIDE A WAY TO FACILITATE THE USER’S NAVIGATION ON THE ROADS. THE PROJECT WAS CARRIED OUT MAINLY THROUGH AGILE METHODOLOGIES SUCH AS SCRUM AND KAMBAM, SPRINTS, DAILY SCRUM AND REVIEW, AND PROGRAMMING TECHNIQUES. THE RESULTS BASED ON DIFFERENT DISCIPLINES, SUCH AS OOP, DATABASE, AND DATA STRUCTURE DEMONSTRATE THAT THE APPLICATION IS CONSTANTLY DEVELOPING, SEEKING TO IMPROVE ROADS AND TIME SPENT IN TRANSIT THROUGH TECHNOLOGY AND SOFTWARE ENGINEERING.